Ancient DNA analysis of mid-holocene individuals from the Northwest Coast of North America reveals different evolutionary paths for mitogenomes. - Yinqiu Cui (Public Library of Science (PLoS), 2013)
To gain a better understanding of North American population history, complete mitochondrial genomes (mitogenomes) were generated from four ancient and three living individuals of the northern Northwest Coast of North America, specifically the north coast of British Columbia, Canada, current home to the indigenous Tsimshian, Haida, and Nisga'a. The mitogenomes of all individuals were previously unknown and assigned to new sub-haplogroup designations D4h3a7, A2ag and A2ah. The analysis of mitogenomes allows for more detailed analyses of presumed ancestor-descendant relationships than sequencing only the HVSI region of the mitochondrial genome, a more traditional approach in local population studies. The results of this study provide contrasting examples of the evolution of Native American mitogenomes. Those belonging to sub-haplogroups A2ag and A2ah exhibit temporal continuity in this region for 5000 years up until the present day. Of possible associative significance is that archaeologically identified house structures in this region maintain similar characteristics for this same period of time, demonstrating cultural continuity in residence patterns. The individual dated to 6000 years before present (BP) exhibited a mitogenome belonging to sub-haplogroup D4h3a. This sub-haplogroup was earlier identified in the same general area at 10300 years BP on Prince of Wales Island, Alaska, and may have gone extinct, as it has not been observed in any living individuals of the Northwest Coast. The presented case studies demonstrate the different evolutionary paths of mitogenomes over time on the Northwest Coast.